Exploring metaverse online platform “Gather.Town” for collaborative learning activities to improve participants’ engagement in adolescent health workshop intervention - Velies, Dyana Safitri; Jocelyn, Jocelyn; Wibowo, Johan; Sungono, Veli (Journal of Community Empowerment for Health, 2025)
Introduction: Health-related behavior in adolescents gives significant impact on their future health and the next generation. Some interventions toward adolescents’ health-related behaviors have resulted ineffectively, owing to status and respect sensitivity in adolescents’ uniqueness. Covid-19 pandemic caused restrictions to face-to-face meetings and educational activities. The "gather.town" metaverse was used to construct an online event platform that included attractive and interactive educational workshops to induce collaborative learning activities for adolescents, as a result of on Human Centered Design process that starts with adolescents and ends with tailored innovative solutions to improve their health. This study aims to explore the use “gather.town” as a metaverse online platform to engage with adolescents during intervention to improve.Methods: The intervention was designed and organized by a student-led organization using a metaverse online platform “gather.town” to reach out to adolescents in Indonesia, consisting of ten workshops, each demonstrating a health topic with a skill-learning approach using interesting activity guided by a pair of knowledgeable speakers. Moreover, “gather.town” offers unique options such as creating individual avatar and interacting with people outside the workshop rooms during the event. The main event was divided into morning and afternoon sessions with a total of 140 adolescents from different areas and educational backgrounds in Indonesia.Results: Only 47% of participants gave feedback through online evaluation from. All participants were satisfied with the workshops. Thirteen percent of participants were unsatisfied with the “gather.town” platform.Conclusion: Using a human-centered design approach to combine skills and health knowledge increases adolescents’ interest to join the intervention. Future interventions may consider exploring other user-friendly platforms and total number of activities to accommodate more participants in each workshop.